Cidade literaturalizada: Salvador e uso estratégico da literatura de Jorge Amado como incentivo ao consumo cultural e suas vantagens nas concorrências intercidades - Souza, Mário César de (2024)
The objective of this research is to comprehend how public and private agents have utilized the urban representations of the city of Salvador, as described by the writer Jorge Amado in his novels, and how these images have been appropriated and redefined through urban marketing. The aim is to provide institutional support to the tourism sector and gain competitive advantages in intercity competition. To underpin our research, we have formulated and developed two concepts: “(re)impression of the city” and “literaturalized city”. This work is divided into three parts. In the first chapter, titled “Brazilian Literature as a Builder of National Identity”, we emphasize the pivotal role that literature plays as an artistic form of expression. Utilizing written language as its primary creative tool, literature has the power to bring to life works that capture the worldviews, emotions, ideas, and experiences of both writers and readers. We underline that, beyond its aesthetic dimension, literature has a relevant function in social and political spheres. It can not only represent and reflect on reality but also actively question, criticize, and influence the social and political aspects of society. Additionally, the study analyzes cultural policies as drivers of development, urban revitalization, and cultural consumption and input. Recognizing the impact of these policies, we seek to understand how they shape and influence literary production, contributing to the construction and representation of national identity through artistic expression. In the second chapter, titled “Marketing: Brief Considerations on Advances and Transformations in Historical Context”, we address the adoption of marketing strategies from the private business sector in public administrations. We observe that such practices have gained ground due to the perception that, to compete in the city landscape, adaptation to the principles of modern capitalism, which values successful city models, is necessary. We argue that urban entrepreneurship has become a potentially irreversible path. In the third chapter, “Jorge Amado and Salvador: Urban Narratives, Speech Places, and Spatial Agency in Literary and Touristic Legacies”, we defend the importance of toponymy in understanding the role of the city of Salvador in the author’s work. We argue that street names, neighborhoods, alleys, and crossroads play a significant role in Amado’s narratives, becoming essential elements of the cultural and social fabric portrayed in his stories. We affirm that these toponymic elements are not mere geographical references but symbols that evoke collective memories, cultural traditions, and local identity. They enrich narratives by providing a poetic dimension to the work, intensifying the drama and adding depth to the world of novelistic literature. We also investigate the intersection between the renowned writer’s work and the tourist scene in Salvador, specifically the various city facilities intrinsically linked to the author, highlighting the Casa do Rio Vermelho, the Espaço Jorge Amado, the Fundação Casa de Jorge Amado, and the Festa Literária Internacional do Pelourinho. Furthermore, we emphasize the importance of gastronomy in Jorge Amado’s literary production, examining its essential function within the scope of culinary tourism in Salvador. We explore the connections between Amado’s rich literary tapestry and the region’s culinary tradition, highlighting its influence on the tourist experience. Additionally, we analyze the use of Jorge Amado’s work as a significant tourist attraction during the Salvadoran carnival, investigating how his narrative and characters integrated into the festive context of the city. Lastly, but not least, we shed light on Jorge Amado’s standpoint, examining how his unique perspective permeates not only his literary works but also influences the city’s tourism image and identity. By considering these elements in an integrated manner, this research aims to provide a comprehensive understanding of the interconnection between Amado’s literary production, tourism, and urban marketing. In the concluding remarks, we affirm that public and private agents have utilized the urban representations of Salvador described by Jorge Amado in his novels, aiming to provide institutional support to the tourism sector and gain competitive advantages in intercity competition. Through this trajectory, the intertwining of fiction and reality becomes an advertising appeal that contributes to the selling process of the product “city of Salvador”.